1979
DOI: 10.1002/1097-0142(197907)44:1<304::aid-cncr2820440151>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Gestational choriocarcinoma and thyrotoxicosis

Abstract: A case of a 26-year-old woman with metastatic choriocarcinoma and clinical and biochemical thyrotoxicosis is described. This represents the eighth reported case of the association of choriocarcinoma and thyrotoxicosis. Serial monitoring of serum thyroxine (T4) and thyroid stimulating hormone (TSH) levels correlated precisely with the beta sub-unit human chorionic gonadotropin (hCG) level and the quantitation of host tumor burden. The development of a hypermetabolic syndrome in patients with choriocarcinoma may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Some studies investigating the effect of high HCG titers on TSH and fT4 levels have shown that when the HCG titer increases above 200,000 IU/l, the probability of incidence of TSH suppression (TSH < 0.2 IU/l) is 67%, while at titers above 400,000 IU/l, TSH suppression reaches 100%. 17 , 18 , 19 In our study, contrary to the data in the literature, there were euthyroid patients with even the highest HCG values. Among the 30 patients with HCG values above 200,000 uIU/l, 17 (70%) began treatment for clear hyperthyroidism, while among the 20 patients with HCG above 400,000 uIU/l, 15 (71%) began treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies investigating the effect of high HCG titers on TSH and fT4 levels have shown that when the HCG titer increases above 200,000 IU/l, the probability of incidence of TSH suppression (TSH < 0.2 IU/l) is 67%, while at titers above 400,000 IU/l, TSH suppression reaches 100%. 17 , 18 , 19 In our study, contrary to the data in the literature, there were euthyroid patients with even the highest HCG values. Among the 30 patients with HCG values above 200,000 uIU/l, 17 (70%) began treatment for clear hyperthyroidism, while among the 20 patients with HCG above 400,000 uIU/l, 15 (71%) began treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Several regimens via propylthiouracil, propranolol, or Lugol's solution, for example, could be effective for counteracting the overactive thyroid function; nonetheless, all the above regimens were in vain for this patient, probably because of the extremely high hCG level which was unexpected. Used for underlying conditions refractory to conventional therapy, the EMA‐CO chemotherapy for patients with very high hCG titers has been very effective, except in a small population with thyrotoxicosis: 6–9 Only the first course relieved our patient's symptoms, and the second resulted in her reaching the euthyroid state before the hCG titer was normalized. After the normalization, two additional courses are usually compulsory for complete eradication of the cancer cells.…”
Section: Discussionmentioning
confidence: 90%
“…Though gestational trophoblastic diseases (GTD) in some patients display a marked elevation of serum T4, T3, and free T4 concentrations, clinical thyrotoxicosis is usually absent. Aside from choriocarcinoma as a cause of thyrotoxicosis, symptomatic evidence of increased thyroid function has been reported in approximately 6% of patients with choriocarcinoma, and it appears that serum hCG levels greater than 100 000 mIU/mL are required to produce clinical evidence of thyrotoxicosis 6–9 …”
Section: Discussionmentioning
confidence: 99%
“…It is also well documented that the biochemical markers of choriocarcinoma and of thyroid function parallel the regression of tumor. [3] After three weeks of chemotherapy, patient's hyperthyroid state was controlled partially and the CVS manifestations were also controlled significantly.…”
Section: Discussionmentioning
confidence: 95%